2017
DOI: 10.3389/fphys.2017.00597
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of Effects of Dofetilide, Sotalol, Quinidine, and Verapamil between Human Ex vivo Trabeculae and In silico Ventricular Models Incorporating Inter-Individual Action Potential Variability

Abstract: Background: In silico modeling could soon become a mainstream method of pro-arrhythmic risk assessment in drug development. However, a lack of human-specific data and appropriate modeling techniques has previously prevented quantitative comparison of drug effects between in silico models and recordings from human cardiac preparations. Here, we directly compare changes in repolarization biomarkers caused by dofetilide, dl-sotalol, quinidine, and verapamil, between in silico populations of human ventricular cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 51 publications
5
48
1
Order By: Relevance
“…7 in (6)). Except for the models including the Bett I K1 formulation, all showed a median APD 90 value that was higher than the mean value reported by Britton et al (29) and O'Hara-Rudy et al (6). Therefore, upscaling relative to G K1, critical may be a strategy to make the repolarization faster and to close the gap between in silico and experimental data.…”
Section: K1 Formulation and Its Effects On Ap Waveformmentioning
confidence: 72%
See 1 more Smart Citation
“…7 in (6)). Except for the models including the Bett I K1 formulation, all showed a median APD 90 value that was higher than the mean value reported by Britton et al (29) and O'Hara-Rudy et al (6). Therefore, upscaling relative to G K1, critical may be a strategy to make the repolarization faster and to close the gap between in silico and experimental data.…”
Section: K1 Formulation and Its Effects On Ap Waveformmentioning
confidence: 72%
“…Simulations were run using G K1 values ranging from 0 (no I K1 ) to 10ÂG K1;critical and increase with 0.25ÂG K1;critical step. The experimental range for APD 50 and APD 90 refers to adult healthy cardiomyocytes from Britton et al(29). To see this figure in color, go online.…”
mentioning
confidence: 99%
“…It must be noted that extensive experimental datasets from healthy adult human cardiomyocytes are non-existent due to unavailability of such cardiac tissue. Thus, inferences could only be made based on donor heart-derived human cells (34, 47, 48) or well-studied adult cardiomyocytes from other species. Nevertheless, different ion channel expressions can lead to underestimation (as for bepridil) or overestimation of the actual toxicity of a drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, each of the models is considerably different in relation to the conductance levels of individual cardiac ion channels. As a result, predictions around APD prolongation and emergence of proarrhythmic markers that each of the models make in response to drug block are significantly different (Mirams et al, 2014 ) and do not reproduce in vivo data (Britton et al, 2017 ). For example, Mann et al showed that 50% inhibition of Kv11.1 caused 113, 22, and 34 ms prolongation of APD 90 for ORD11, TT06 and GB10 respectively (Mann et al, 2016 ).…”
Section: Multichannel Pharmacologymentioning
confidence: 99%